Carlos Gutierrez-Noriega and his contribution to the Peruvian Medical Shool - AYALA, SALOMÓN (2004)
This study presents an approach to the scientific and intellectual work of master Carlos GutiérrezNoriega whose labor developed during the 30’s and 40’s, period of major development and social genuineness of Peruvian Medicine. Founder of the Pharmacology in Peru and initiator of this specialty national character study. The review focuses his teaching labor and outstanding scientific contribution in the fields of experimental psychiatry, ethnopharmacology and general pharmacology, as well as, his investigations on cocaism and cocaine, his studies about indigenousness and the Cervantes role in medicine. It emphasizes his brilliant path values as a vital force in the university institutional development.